Analisis Hots Pada Pre-Activity Dalam Buku Siswa “English Skills For The Future” Kelas XII - Siti Aisyah Nur Aini; Sri Handayani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This study aims to analyze the distribution of Higher Order Thinking Skills (HOTS) in each question on pre-activity in the student book entitled